2017
DOI: 10.1016/j.neuroscience.2017.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Cellular circadian oscillators in the suprachiasmatic nucleus remain coupled in the absence of connexin-36

Abstract: In mammals, the master circadian clock resides in the suprachiasmatic nucleus (SCN). The SCN is characterized by robust circadian oscillations of clock gene expression and neuronal firing. The synchronization of circadian oscillations among individual cells in the SCN is attributed to intercellular coupling. Previous studies have shown that gap junctions, specifically those composed of connexin-36 (Cx36) subunits, are required for coupling of electrical firing among SCN neurons at a time scale of milliseconds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…This shows that glial Cx43 and Cx30 are dispensable for circadian rhythm generation. This is in contrast to changes in period length of circadian rhythms in locomotor activity observed in Cx36-deficient mice [28, 29]. Thus, in the SNC Cx36-mediated neuronal coupling is functionally more important than glial coupling through Cx30 or Cx43.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This shows that glial Cx43 and Cx30 are dispensable for circadian rhythm generation. This is in contrast to changes in period length of circadian rhythms in locomotor activity observed in Cx36-deficient mice [28, 29]. Thus, in the SNC Cx36-mediated neuronal coupling is functionally more important than glial coupling through Cx30 or Cx43.…”
Section: Discussionmentioning
confidence: 96%
“…Within the SCN, neuronal gap junctions are important for electric coupling, which is crucial to generate a coherent circadian rhythm of neuronal firing [27]. Importantly, deletion of neural connexin Cx36 significantly impairs the SCN electric coupling resulting in changes of circadian period length [28, 29]. Moreover, astrocytic-neuronal signalling regulates rhythmic SCN neuronal activity and thus circadian rhythm generation [30].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, astrocytes form a syncytium, via gap junctions, that allow the propagation of small signaling molecules through the glial network ( 69 ). Pharmacological inhibition of gap junctions in SCN slides ( 70 , 71 ) and mouse models with deletion of the neuronal connexin-36, impairs the circadian pattern of neuronal activity without affecting the long-term synchronization of clock gene expression ( 72 ) and with mild effect on behavioral rhythms ( 73 ). Similarly, studies in mouse models with deletion of astrocytic specific connexins indicate that the astrocytic coupling in the SCN is dispensable for circadian rhythm generation and light-entrainment ( 74 ).…”
Section: Astrocyte Circadian Clocksmentioning
confidence: 99%
“…Connexin36 is a subunit of gap junctions specifically expressed in neurons, and it has been shown that inhibiting the function of gap junctions eliminates electrical coupling among SCN neurons and deleting connexin36 decreases the amplitude of daily rhythms in behaviour (Long et al., ; Wang, Chen & Wang, ). However, recent work reveals that loss of connexin36 in adult mice does not impair circadian function at the behavioural or molecular levels (Diemer et al, ). Collectively, these results suggest that signalling through connexin36–expression gap junctions modulates short‐term electrical coupling among SCN neurons, but this mechanism is not necessary for long‐term synchronization among SCN neurons at the level of the molecular clock.…”
Section: Scn Cellular Developmentmentioning
confidence: 99%